Effect of Ceftriaxone and Timentin antibiotics on morphogensis in the in vitro culture of bread wheat Triticum aestivum L. - Bannikova, M.A.; Gorbatyuk, I.R.; Hnatiuk, I.S.; Malysheva-Otto, L.V.; Duplij, V.P. (Вiopolymers and Cell, 2016)
Aim. To study the influence of antibiotics Ceftriaxone and Timentin on the morphogenic calli and roots formation, shoots regeneration in two bread wheat cultivars Triticum aestivum L., to study effect of Ceftriaxone on the growth dynamics of plants. Methods. In vitro plant tissue culture, analysis of Variance, correlation and regression analysis. Results. The influence of β-lactam antibiotics Ceftriaxone and Timentin on morphogenetic processes (morphogenic calli formation, shoots regeneration and rhizogenesis), was studied in apical 18-day-old wheat calli. Two wheat genotypes of different growth habits, winter and winter-spring, were used. Conclusions. Timentin and Ceftriaxone stimulate morphogenic calli formation in bread wheat apical calli. As compared to Timentin, Ceftriaxone has strong concentration-dependent and genotype-dependent influence on shoots regeneration. The roots formation depended primarily on the wheat genotype, independently from an antibiotic applied. The presence of Ceftriaxone in culture medium stimulates rooting and growth of regenerating plants as well as their biomass increment.